Is leasing a debt? According to suspension of debt payment obligations law - Suwinto Johan (Universitas Muhammadiyah Magelang, 2022)
Every company wants to grow and in order to achieve that, a company needs funding. There are various ways for a company to get funding, be it external or internal. One alternative form of funding is leasing. Leasing is the rental of production equipment by the company (lessee) to the lessor. The company should pay rental fees. Leasing has several advantages over loan financing. The rental fee will be charged at the company's expense. As for loans from financial institutions, only interest costs are charged as fees. This study examines the status of leasing or leasing in companies experiencing bankruptcy. This study uses a normative legal method associated with the company's capital structure theory. This study concludes that the lease is not part of the debt. A lease is a form of a rental contract. Leases do not have a record as a debt on the company's balance sheet. In addition, the guarantee or production equipment leased is the property of the lessor or the lessor. The company does not have the right to own the machines until it is fully paid off. Unpaid rent that is past due can be included in an expense bill like any other expense.